Urgensi Pendidikan Agama Islam Dalam Menghadapi Fenomena Intoleransi Antar Umat Beragama - Karimah, Abidatul; Fadli, Failasuf (LP3M STAI Ibnurusyd, 2023)
The purpose of this study is to determine the implementation of tolerance by people who live amongdiversity in a country. Tolerance is the most appropriate attitude in dealing with various kinds ofdifferences that exist, this attitude will also create peace and harmony among people. Indonesia is alarge country rich in diversity of religions, ethnicities, cultures and regional languages. However, withthese differences, the attitude of its citizens is even wrong. Communities that used to prioritizetogetherness and harmony, now tolerance has turned into individualism and the loss of mutual respectfor fellow citizens. Of course, this trait is very detrimental and contradicts our motto, namely the mottoBhinneka Tunggal Ika, which means that although we are different, we are still one. This differenceshould create a spirit of unity that we have and need to protect and be able to make the nationstronger because it is able to live side by side with all the diversity and differences in it. The importantrole of Islamic Religious Education is in realizing and fostering the spirit of unity and unity of theIndonesian nation by providing an understanding of togetherness that we must protect as people ofGod Almighty and as the duty of Indonesian citizens.